Studies on Dissipation Pattern of Diafenthiuron on Cauliflower - Jemimah, N.; Sridevi, G.; Anitha, V.; Aparna, B.; Devi, G. Uma; Kumar, M. V. Nagesh (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during rabi season of October, 2019 to February, 2020 at College Farm, College of Agriculture, Rajendranagar, Professor Jayashankar Telangana Agricultural University (PJTAU) to determine the dissipation pattern of Diafenthiuron in Cauliflower. Diafenthiuron 50 WP @ 300 g a.i. ha-1 was sprayed twice at 15 days interval during the curd initiation stage. The cauliflower curds were collected at 0 (2 hrs after spray), 1, 3, 5, 7, 10, 15, 20 and 25 days after second spray. The samples were brought to the Laboratory of AINP on Pesticide Residues, PJTAU where dissipation studies were carried out. Extraction and cleanup of the samples was done following the validated QuEChERS method and the residues were quantified on Liquid Chromatography Mass Spectrometry (LC-MS/MS). The limit of quantification (LOQ) of this method was 0.05 mg kg-1. The analytical method adopted for analysis on LC-MS/MS was evaluated through linearity, LOD, LOQ, fortification and recovery studies. Linearity studies gave satisfactory R2 value of 0.998, while the fortification studies recorded recovery in the acceptable range of 98.31-101.52 per cent. The results indicated that the mean initial deposit of 5.356 mg kg-1 recorded at 0 days (2 hrs) in cauliflower curds after second spray dissipated to 0.227 mg kg-1 by 10th day and to below LOQ by 15th day after final spray with calculated half-life of 2.33 days.